AGRO-ECOLOGICAL PECULIARITIES OF NATURAL BRINES AND MINERALS’ IMPACT ON SOIL MICROORGANISMS - Pysarenko, P.; Samoilik, M.; Dychenko, O.; Taranenko, А.; Galytska, M.; Nimets, O. (Scientific Progress & Innovations, 2022)
Under modern conditions of energy and environmental crisis, the search for new substances ensuring the formation of microbial cenosis composed of many valuable groups of microorganisms, having the optimal level of humification and increasing the organic substance in the soil, make it possible to develop innovative environmentally safe kinds of fertilizers and crop protection means under specific soil and climatic conditions. At the same time, at present, studying the effect of different doses of concomitant layer water on microbiological and enzymatic soil activity for substantiating environmentally safe system of applying new kinds of fertilizers and plant protection means is topical and insufficiently investigated. Therefore, the main purpose of this paper is studying the specifics of formation and functioning microbial cenosis and establishing the dependence between microbiological and enzymatic activity of podzolized black soil at using concomitant layer water of different concentration. The experiment envisaged researching the effect of concomitant layer water of different doses: 300, 600, 900, 1,200, 2,400, 4,800 l/ha on the amount of major microorganism groups in the soil. Soil without applying any substances was considered as a control variant. As a result of studying major environmental trophic groups of microorganisms, it has been found that the use of concomitant layer water at a dose of 1,200 l/ha assists in increasing nutrients in the soil for various environmental trophic groups of microorganisms, decreasing humus decomposition speed, and creating favorable conditions for developing soil microorganisms. It has been established that the use of concomitant layer water at a dose of 400 l/ha improves soil enzymatic activity for 21 days (in particular, that of polyphenol oxidase, peroxidase, catalase, and urease). The number of ammonification and nitrogen fixing bacteria at applying concomitant layer water at a dose of 1,200 l/ha increases immediately after using. Then, during the following months their amount decreases to the control level. Applying high doses of concomitant layer water – 4,800 l/ha results in decreasing these groups of bacteria. Concomitant layer water at doses from 300 l/ha to 900 l/ha has the highest effect for pedotrophic microorganisms (30.2; 29.4, and 17.1 million, respectively), and for oligonitrophic – 900–1,200 l/ha (5.4 and 6.0 million, respectively). Thus, the application of concomitant layer water at a dose of 1,200 l/ha can be used as environmentally safe fertilizer in organic farming, which will favor the improvement of soil and biological indicators of land.